Coursenotes_ECON301

# 3 ross phoebe joey monica rachel and chandler have the

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ot to scale, but label the diagram completely). 108 ECON 301 LECTURE #7 WALRAS LAW Is there a particular reason that we can solve the equilibrium price ratio from the market equilibrium condition of either good X or good Y? Remember, in our example we got the same value for _ PX__ = 3/5 from the PY market equilibrium condition of both good X and good Y. This is not a coincidence! Indeed, it comes from a general theoretical result, namely, Walras Law. Walras Law can be stated in the context of a pure exchange economy as follows: If the market for one good (say, good Y) is in equilibrium, then the market for the other good (i.e. good X) is also in equilibrium. Walras Law states that if the market for good X is already in equilibrium, then so is the market for good Y. Therefore, if we have already solved for the equilibrium price ratio from the market equilibrium equation of good X, then we do not need to solve the other market equilibrium equation since it will be in equilibrium as well (and give us the same answer in terms of the equilibrium price ratio...needless suffering). The logic behind Walras Law lies in the close relationship between the two concepts of consumer equilibrium and market equilibrium. It is not difficult to show (prove) that Walras Law works within the context of the pure exchange economy. To do so, we start with the individual budget constraints PX XA + PY YA = PX XA + PY YA PX XB + PY YB = PX XB + PY YB If we sum these two budget constraints together, we get... PX (XA + XB) + PY (YA + YB) = PX (XA + XB) + PY (YA + YB) [market X] [market Y] [endowment X] [endowment Y] PX X + PY Y = PX X + PY Y PX (X X) + PY (Y Y) = 0 (10) Now, let's suppose the market for good X is in equilibrium already. That is the aggregate demand = the aggregate supply of X. 109 XA + XB = X [market X] X = X X X = 0 Thus, PX (X X) = 0 "excess demand" = 0 "value of excess demand" = 0 Substituting this result into (10), we get: PX (X X) + PY (Y Y) = 0 PY (Y Y) = 0 Y Y = 0 Y = Y (10) "value of excess demand" = 0 "excess demand" = 0 "demand" = "supply" And the...
View Full Document

## This note was uploaded on 05/25/2010 for the course ECON 301 taught by Professor Sning during the Spring '10 term at University of Warsaw.

Ask a homework question - tutors are online